Nonlinear Behaviour and Stability of Thin-Walled Shells - Obodan, Natalia I.; Lebedeyev, Olexandr G.; Gromov, Vasilii A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book focuses on the nonlinear behaviour of thin-wall shells (single- and multilayered with delamination areas) under various uniform and non-uniform loadings. The dependence of critical (buckling) load upon load variability is revealed to be highly non-monotonous, showing minima when load variability is close to the eigenmode variabilities of solution branching points of the respective nonlinear boundary problem. A novel numerical approach is employed to analyze branching points and to build primary, secondary, and tertiary bifurcation paths of the nonlinear boundary problem for the case of uniform loading. The load levels of singular points belonging to the paths are considered to be critical load estimates for the case of non-uniform loadings.
1. In lieu of introduction -- 2. Boundary problem of thin shells theory -- 3. Branching of nonlinear boundary problem solutions -- 4. Numerical method -- 5. Nonaxisymmetrically loaded cylindrical shell -- 6. Structurally nonaxisymetric shell subjected to uniform loading -- 7. Postcritical branching patterns for cylindrical shell subjected to uniform external loading -- 8. Postbuckling behaviour and stability of anisotropic shells -- 9. Conclusion.
Keywords: Engineering; Computer science -- Mathematics; Engineering mathematics; Mechanical engineering; Astronautics; Engineering; Structural Mechanics; Mechanical Engineering; Appl.Mathematics/Computational Methods of Engineering; Aerospace Technology and Astronautics; Computational Mathematics and Numerical Analysis